2020
DOI: 10.1080/19186444.2020.1768794
|View full text |Cite
|
Sign up to set email alerts
|

Analysing competitiveness and trade performance: evidence from Indian textile industry and its select competitors

Abstract: The present study investigates the trade performance and competitiveness of textile industry of India and its competitors namely China and Vietnam by using revealed comparative advantage developed by Balassa, and other trade parameters given by World Bank in terms of growth, diversification and sophistication for 1988 to 2016. Data has been taken from World Integrated Trade Solution (WITS) based on harmonised system (HS-2) including 11 products ranging from HS-50 to HS-60. Results indicate that India has attai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…The present findings seem to be consistent with other research which found that Türkiye and other Asian countries have a great trade competitiveness in the world's textile industry (Bostan et al, 2010;Erkan, 2013;Guan et al, 2019;Gautam & Lal, 2020;Halife, 2022). It is believed that the findings obtained from this study provide valuable insights into the trade competitiveness of nations for decision-makers and policymakers in the textile industry.…”
Section: Conclusion and Discussionsupporting
confidence: 92%
“…The present findings seem to be consistent with other research which found that Türkiye and other Asian countries have a great trade competitiveness in the world's textile industry (Bostan et al, 2010;Erkan, 2013;Guan et al, 2019;Gautam & Lal, 2020;Halife, 2022). It is believed that the findings obtained from this study provide valuable insights into the trade competitiveness of nations for decision-makers and policymakers in the textile industry.…”
Section: Conclusion and Discussionsupporting
confidence: 92%
“…In the labor‐intensive textile and capital‐intensive electronics industries, Vietnam and China are falling behind in technical development (Chiu, Lin, & Yang, 2019). Vietnamese researchers examined the international competitiveness of Vietnam's garment and textile industries and concluded that Vietnam was less competitive than China in the four components of the Generalized Double Diamond Model analysis (factor conditions; demand conditions; related and supporting industries; and company strategy, structure, and competitive environment) (Gautam & Lal, 2020; Guan, Xu, Jiang, & Jiang, 2018; Vu & Pham, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…After Balassa, it has become the index most used in the literature. More recently, [18,19,20,21,22] undertook studies to analyse sector-specific and country-specific competitiveness using the RCA approach. Although Vollrath [17] solved the problem of symmetry by taking the logarithm of the RCA, he did not solve the problem of RCA being undefined; because when a country's export in a particular product is zero, the RCA index is undefined.…”
Section: Many Methods Have Been Developedmentioning
confidence: 99%